2014
DOI: 10.1007/s10916-014-0164-4
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones in Medicine: Emerging Practices in an Academic Medical Center

Abstract: Advances in mobile phone technology now provide a myriad of resources to physicians' fingertips. However, the medical profession continues to struggle with potential for misuse of these devices. There is a need for better understanding of physicians' uses of smartphones in order to establish guidelines for appropriate and professional behavior. The purpose of the current study was to survey physicians' and medical students' practices concerning smartphone use in the healthcare setting. Physicians and medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 11 publications
1
44
0
Order By: Relevance
“…[17] Recent study reveals that physicians and medical students make decisions about using their Smartphones according to some combination of three considerations: Degree of relevance to patient care, the appropriateness of the behavior in front of patients, and the issue of how disruptive that behavior may be. [18] There is a perceived risk that portable devices may distract from the provision of patient or client care if used by health professionals or students during employment. [19] The present study mobile technology was extensively used for social communication.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Recent study reveals that physicians and medical students make decisions about using their Smartphones according to some combination of three considerations: Degree of relevance to patient care, the appropriateness of the behavior in front of patients, and the issue of how disruptive that behavior may be. [18] There is a perceived risk that portable devices may distract from the provision of patient or client care if used by health professionals or students during employment. [19] The present study mobile technology was extensively used for social communication.…”
Section: Discussionmentioning
confidence: 99%
“…After deduplication and iterative review of abstracts and full texts, 14 articles were identified as meeting the inclusion criteria, 8 of which were original research articles [9,[17][18][19][20][21]26,39]. Five were magazines articles (all coming from the USA) [16,[22][23][24]27] and one a viewpoint journal article [25].…”
Section: Resultsmentioning
confidence: 99%
“…All the publications were from high-income countries as follows: nine from the USA [9,16,19,20,[22][23][24]27,39], two from the UK [25,26], two from Canada [17,18] and one from Ireland [21]. The identified review articles were published between 2012 and 9 2016: one in 2012 [20], two in 2013 [23,27], five in 2014 [16,17,21,24,25], two in 2015 [19,22], and four in 2016 [9,18,26,39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations